Sustained Activity of Metabotropic Glutamate Receptor: Homer, Arrestin, and Beyond - Geehoon Chung; Sang Jeong Kim (Neural Plasticity)
When activated, metabotropic glutamate receptors (mGlus) exert long-lasting changes within the glutamatergic synapses. One mechanism is a tonic effect of downstream signal transduction pathways via sustained activation of mGlu itself. Like many other G protein-coupled receptors (GPCRs), mGlu can exist in a constitutively active state, which persists agonist independently. In this paper, we review the current knowledge of the mechanisms underlying the constitutive activity of group I mGlus. The issues concerning Homer1a mechanism in the constitutive activity of group I mGlus and recent findings regarding the significant role of β-arrestin in sustained GPCR activity are also discussed. We propose that once in a state of sustained activation, the mGlu persistently activates downstream signaling pathways, including various adaptor proteins and kinases, such as β-arrestin and mitogen-activated protein kinases. In turn, these effector molecules bind to or phosphorylate the mGlu C-terminal binding domains and consequently regulate the activation state of the mGlu.